New Imperialism: Toward a Holistic Approach. Issue 2 (15th April 2013) - Kettell, Steven; Sutton, Alex
Abstract : A prominent theme in scholarly analyses of contemporary international affairs concerns the extent to which the unrivalled power and activities of the United States can be said to constitute a form of imperialism. Typically, the contours of this debate center on the ostensible differences between "old" and "new" varieties of imperialist practice. Yet the concept of "new imperialism" remains one on which little consensus exists. Wide differences of opinion on its origins, dynamics, and characteristics are evident, as is an analytical bifurcation between distinct "economic" and "geopolitical" explanations. This absence of conceptual unity leads to accounts of new imperialist strategy that are partial, limited, and incomplete. If the theoretical value of new imperialism is to be realized, a more holistic approach is needed. To this end, some of the key differences between the contexts of new and old imperialism are explored.